Islamic abstractive motifs interpretation in Persian art: A historical study of Herat school painting / Neda Zoghi - Neda , Zoghi (2019)
Features of Persian art including meticulous designs, great complexity and the romantic and heroic stories illustrated in the paintings in the 15th century underwent drastic changes in Herat. One of the most distinctive features of the Herat School was its continual use of various decorative motifs in painting. The Herat style in Persian art emerged with the Timurids under the patronage of Shahrukh who contributed remarkably to social and cultural developments in Iran. By delving deeply into the works of the early centuries of Islam to the present, one can perceive that it is the “ornament” that is of a special position in the Herat School of Islamic art as the most important school in the Timurid Dynasty and Persian painting history, for the development of forms and colours in Persian forms with Chinese influence in the Mongol Dynasty. The objectives of this research include analysing Islamic motifs in Persian painting, studying the theoretical foundations of Islamic motifs and Persian painting schools to examine the causes of the creation of the Islamic art motifs in the Herat School of Painting. The researcher analysed five paintings from Shahnameh-y-Baysonquri by using Panofsky’s theory about iconography and iconology to interpret Islamic motifs used in the Herat School of Painting. The researcher found affective factors in the Herat School for abstractive motifs and explained their meaning. The research adopts a qualitative based on library research using journals articles, art and art history books. Persian painters in the Timurid Dynasty used arabesque, geometric and Khataee motifs as decorations. Iranian painters created movement, rhythm, emotion, space and the relationship between them using arabesque shapes to represent the beauty of objects that is inherent to the beauty of God. The principle of monotheism is the most significant codification of the abstract geometric, Eslimee and Khataee decorative designs and Islamic thought influenced Iranian painting significantly.